THE BAURU BASIN IN SÃO PAULO AND ITS TETRAPODS - Langer, Max C.; Delcourt, Rafael; Montefeltro, Felipe C. [UNESP]; Silva Junior, Julian C.G.; Soler, Mariana G.; Ferreira, Gabriel S.; Ruiz, Juan V. [UNESP]; Barcelos, Lucas A.; Onary, Silvio; Marsola, Júlio C.A.; Castro, Mariela C.; Cidade, Giovanne M. [UNESP]; et al. (Derbyana, 2022)
The Bauru Basin bears one of the best sampled tetrapod paleofaunas of Brazil, with about 70% of this diversity collected from its deposits in São Paulo. Its fossils are known since the beginning of the 20th century, coming from all stratigraphic units of the Basin cropping-out in the state, i.e., Santo Anastácio, Araçatuba, Adamantina (alternatively divided into Vale do Rio do Peixe, Presidente Prudente, and São José do Rio Preto formations), and Marília formations. Identified taxa include rare anurans, mammals, and squamates, an important set of testudines, theropods (including birds), and sauropods, in addition to one of the most diverse crocodyliform faunas known worldwide. This congregates more than fifty unique taxonomic entities, including 42 formally described species. Based on biostratigraphic correlations (including tetrapods), on few absolute ages, and other sources of evidence, the Bauru Basin deposits in São Paulo seem to be chronologically restricted to the Late Cretaceous, but further investigation is much needed. Finally, the history of research with such fossils highlights the importance of public funding for research and decentralization of university education for the advancement of science.
A BACIA BAURU NO ESTADO DE SÃO PAULO E SEUS TETRÁPODES.
Keywords: Bauru Basin; Cretaceous; São Paulo; Tetrapoda